PEMBINAAN CLCK DALAM PROGRAM PENYUSUNAN RPP UNTUK MENINGKATKAN KOMPETENSI GURU KKM MI KECAMATAN SUKODONO - ISTIQOMAH ISTIQOMAH (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2022)
The research was conducted in two cycles, each cycle consisting of four stages, namely: planning, implementing, observing and reflecting. The specified performance indicator is a minimum score of 12 (active enough). In the preparation of the RPP, it can be said that the actions implemented were successful. The aspects measured in the observation were the enthusiasm of the teachers who were members of the KKM, Sukodono Subdistrict, Lumajang Regency, the teacher's interaction with the school superintendent, interaction with the teacher in the KKG, group cooperation, activities in group discussions. From the analysis it was found that there was an increase in teacher activity and competency in preparing lesson plans from cycle I to cycle II. Achievement of performance indicators is in action II. Thus, it can be assumed that the CLCK Guidance Model in the RPP preparation program can increase the competence of teachers, especially those who are members of the KKM Sukodono District, Lumajang Regency. Teachers gave a positive response to CLCK coaching in the lesson plan preparation program. Thus it can be suggested to supervisors or other researchers that the CLCK Development Model in the RPP preparation program is still implemented on an ongoing basis. ABSTRAKPenelitian dilakukan dengan dua siklus masing-masing siklus terdiri atas empat tahapan, yakni : perencanaan, pelaksanaan, observasi dan refleksi. Indikator kinerja yang ditetapkan adalah bila minimal skor 12 (cukup aktif). Dalam penyusunan RPP, maka sudah dapat dikatakan tindakan yang diterapkan berhasil. Aspek yang diukur dalam observasi adalah Antusiasme Guru yang tergabung dalam KKM Kecamatan Sukodono Kabupaten Lumajang, interaksi Guru dengan pembina pengawas sekolah, interaksi dengan Guru dalam KKG, Kerja sama kelompok, aktivitas dalam diskusi kelompok. Dari analisis diperoleh bahwa terjadi peningkatan aktivitas dan kompetensi guru dalam menyusun RPP dari siklus I ke siklus II. Ketercapaian indikator kinerja terdapat pada tindakan ke II. Dengan demikian, dapat diumpamakan bahwa Model Pembinaan CLCK dalam program penyusunan RPP dapat meningkatkan kompetensi guru khususnya yang tergabung dalam KKM Kecamatan Sukodono Kabupaten Lumajang. Guru memberikan respon positif terhadap pembinaan CLCK dalam program penyusunan RPP. Dengan demikian dapat disarankan kepada pengawas atau peneliti yang lain agar Model Pembinaan CLCK dalam program penyusunan RPP tetap dilaksanakan secara berkesinambungan.